Kemampuan siswa dalam memecahkan masalah program linear: Sistematik literatur review - Lia Halimatus Sadiah; Dadang Juandi; Tatang Herman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Linear programming is a contextual material in mathematics learning. But there are facts that show that there are still mistakes and difficulties experienced by students in linear programming problems. This study aims to conduct a literature review on mathematical abilities of students, errors and difficulties in linear programming problems. This study uses the SLR (Systematic Literature Review) research method. Data collection in this study was carried out by documenting and reviewing all articles regarding mathematical abilities of students, errors and difficulties on linear program problems published in the 2016-2022 period. This study used 40 accredited articles obtained from Google Scholar and Scopus. Based on this research, it was found that mathematical abilities of students to solve linear programming problems was still low. Students still make many errors in drawing conclusions and encoding errors, and still have difficulties in understanding concepts, making mathematical models and performing correct mathematical procedures.